Silagens de brachiaria brizantha sem aditivo, adicionada de cana de acúcar e aditivos bacterianos - Cristiano Gonzaga Jayme (2010)
This experiment was carried out to estimate the fermentation, fermentation kinetics estimated by semi-automated in vitro gas production technique and the voluntary intake, apparent digestibility,nitrogen balance and fibrous fractions of silages of Brachiaria brizantha cv Marandu without additives (T1), B. brizantha cv Marandu + inoculant Sil-ALL C4 (T2), B. brizantha cv Marandu + inoculant Bactosilo C Tropical (T3) and B. brizantha cv Marandu + 30% of Sugar cane (T4) in sheep. Silages with sugar cane had the lowest pH values among treatments. There were no differences among silages regarding ADF, cellulose and lignin, which remained steady during the period of fermentation. One observed variation in the concentrations of hemicelluloses during thefermentation process in the silages added with Tropical Bactosilo C and sugar cane where the values had varied of 24.56% 34.07% and 23.65% 32.44%, respectively. The comparation among silages in the different periods of fermentation indicated silarity cumulative gas production, except with 24 hours where silage of theT4 (93,43 mL/g de MS) presented highest value (p<0.05). The dry matter degradability (DMD) where highest to T4 in relation to the others treatments in the times of6, 12, 24 and 48 hours with values of 22.67%; 27.69%; 43.54% e 61.04%, respectively. After 96 hours incubation were: 62.75 % to T1 silage, 62.91 % to T2 silage, 62.08 % to T3 silage and 64.64 % to T4 silage, being similar between itself (p>0.05). The highest maximum gas productionpotentials was 188.98 mL/g of dry matter to T1 silage and the lowest to 188.98 mL/g of DM to T2. The lowest time of colonization was for T4 (2.92 h), being different of the others (p<0.05). The T4 presented lowest effective degradabilities (ED) for all the taxes evaluated (46.29% and 27.47% for taxes of 2%/h and 5%/h, respectively). There were no differences among silages regarding voluntary intake of dry matter (VIDM), crude protein (VICP), crude energy (VICE), digestibleenergy (VIDE) and metabolizable energy (VIME) (p>0,05). The largest apparent digestibility of dry matter, crude protein and crude energy was observed for T2, being 60.8%, 44.2% and 57.5%, respectively and the smallest for T4 with 52.9%, 29.9% and 49.5%, respectively (p<0,05). Alltreatments showed positive nitrogen balance and did not differ among them. The additives used did not promote improvements in the qualitative fermentation parameters and the parameters of kinetic degradation by semi-automated in vitro gas production technique of the evaluated silages.The use of incoculant or sugar cane, did not result in voluntary intake increase of dry matter, fibrous fractions and energy of silages.